Biological Planning of Radiation Dose Based on In Vivo Dosimetry for Postoperative Vaginal-Cuff HDR Interventional Radiotherapy (Brachytherapy) - Tamer Soror; Ramin Chafii; Valentina Lancellotta; Luca Tagliaferri; György Kovács (Biomedicines, 2021)
(1) Background: Postoperative vaginal-cuff HDR interventional radiotherapy (brachytherapy) is a standard treatment in early-stage endometrial cancer. This study reports the effect of in vivo dosimetry-based biological planning for two different fractionation schedules on the treatment-related toxicities. (2) Methods: 121 patients were treated. Group A (82) received 21 Gy in three fractions. Group B (39) received 20 Gy in four fractions. The dose was prescribed at a 5 mm depth or to the applicator surface according to the distance between the applicator and the rectum. In vivo dosimetry measured the dose of the rectum and/or urinary bladder. With a high measured dose, the dose prescription was changed from a 5 mm depth to the applicator surface. (3) Results: The median age was 66 years with 58.8 months mean follow-up. The dose prescription was changed in 20.7% of group A and in 41% of group B. Most toxicities were grade 1–2. Acute urinary toxicities were significantly higher in group A. The rates of acute and late urinary toxicities were significantly higher with a mean bladder dose/fraction of >2.5 Gy and a total bladder dose of >7.5 Gy. One patient had a vaginal recurrence. (4) Conclusions: Both schedules have excellent local control and acceptable rates of toxicities. Using in vivo dosimetry-based biological planning yielded an acceptable dose to the bladder and rectum.